Release characteristics of potassium and chlorine for torrefied wheat straw during a combined pyrolysis-combustion system. (September 2020) - Zhang, Shuping; Min, Ganggang; Wang, Junyi; Zhu, Shuguang; Zhang, Houlei; Liu, Xinzhi
Highlights: Release rate of Cl was significantly higher than K during torrefaction process. Pyrolysis temperature of 700 ℃ for pyrolysis-combustion system was suitable. Release characteristics of K/Cl for torrefied samples at 400–800 ℃ were observed. Abstract: The objective is to investigate the release characteristics of potassium (K) and chlorine (Cl) for torrefied wheat straw during a combined pyrolysis-combustion system. Powder and flake wheat straw samples were torrefied at different temperature of 200–300 ℃. The basic characteristics of torrefied samples and the K and Cl release rates of torrefied samples and their char samples derived from pyrolysis at 400–800 ℃ were analyzed and characterized. The results indicated that release rate of Cl was significantly higher than that of K under the same torrefaction conditions. In order to keep most of K and Cl remaining in biochar as well as the volatiles were completely released, the pyrolysis temperature of 700 ℃ for pyrolysis-combustion system was suitable. The total release rate of K and Cl at the pyrolysis temperature of 700 ℃ both exhibited a change trend of decreasing first and then increasing with the increase of torrefaction severity.